دراسة تأثير التنوع الحيوي النباتي في تنوع الطيور في موقع البراج – بانياس الساحل (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تأثير التنوع الحيوي النباتي في تنوع الطيور في بعض المجموعات الحرجية الطبيعية في موقع البراج في منطقة بانياس الساحل. أظهرت الدراسة بان كلاً من طبقة الأشجار والشجيرات ذات أهمية كبيرة بالنسبة للطيور, وخاصة الطيور التي تتكاثر في المواقع. كما بينت وجود علاقة ارتباط قوية بين التغطية النباتية وتنوع الطيور, لاسيما تلك المتخصصة بالغابات. كذلك خلصت الدراسة إلى أن تشابه بعض الخصائص النباتية مثل التغطية والتركيب النباتي في المواقع يؤدي إلى تشابه في تنوع الطيور, وان مراحل التعاقب المتقدمة للنبت ذات أثر ايجابي على الغنى النوعي للطيور واقترحت الدراسة العمل على تشجيع كل ما يساعد في الحفاظ على الطيور وتنوعها. This research aims to study the effect of the forest stand characteristics on the bird diversity in some natural sites in Al-Brage region. The study showed that tree and shrubs layer are very important for the birds, specially forest breeding bird species. It also indicated the presence of a strong relationship between the vegetation cover and the bird diversity , especially forest birds.  The study also showed that the similarity of some vegetation characteristics as cover and composition in the sites lead to similar bird diversity. Furthermore, the advanced succession stages had a positive effect on species richness . The study suggests the encouragement of all what helps in the preservation of the birds and their diversity .